Ovotoxicants 4-vinylcyclohexene 1,2-monoepoxide and 4-vinylcyclohexene diepoxide disrupt redox status and modify different electrophile sensitive target enzymes and genes in Drosophila melanogaster. - Abolaji, A.O.; Kamdem, J.P.; Lugokenski, T.H.; Farombi, E.O.; Souza, D.O.; da Silva Loreto, E.L.; Rocha, J.B. (Redox biology, 2015)
The compounds 4-vinylcyclohexene 1,2-monoepoxide (VCM) and 4-Vinylcyclohexene diepoxide (VCD) are the two downstream metabolites of 4-vinylcyclohexene (VCH), an ovotoxic agent in mammals. In addition, VCM and VCD may be found as by-products of VCH oxidation in the environment. Recently, we reported the involvement of oxidative stress in the toxicity of VCH in Drosophila melanogaster. However, it was not possible to determine the individual contributions of VCM and VCD in VCH toxicity. Hence, we investigated the toxicity of VCM and VCD (10-1000µM) in flies after 5 days of exposure via the diet. Our results indicated impairments in climbing behaviour and disruptions in antioxidant balance and redox status evidenced by an increase in DCFH oxidation, decreases in total thiol content and glutathione-S-transferase (GST) activity in the flies exposed to VCM and VCD (p<0.05). These effects were accompanied by disruptions in the transcription of the genes encoding the proteins superoxide dismutase (SOD1), kelch-like erythroid-derived cap-n-collar (CNC) homology (ECH)-associated protein 1 (Keap-1), mitogen activated protein kinase 2 (MAPK-2), catalase, Cyp18a1, JAFRAC 1 (thioredoxin peroxidase 1) and thioredoxin reductase 1 (TrxR-1) (p<0.05). VCM and VCD inhibited acetylcholinesterase (AChE) and delta aminolevulinic acid dehydratase (?-ALA D) activities in the flies (p<0.05). Indeed, here, we demonstrated that different target enzymes and genes were modified by the electrophiles VCM and VCD in the flies. Thus, D. melanogaster has provided further lessons on the toxicity of VCM and VCD which suggest that the reported toxicity of VCH may be mediated by its transformation to VCM and VCD.